Refractive error among school children in Jhapa, Nepal - Gauri Shankar Shrestha; Digen Sujakhu; Purushottam Joshi (Journal of Optometry, 2011)
Purpose: To evaluate the pattern of refractive errors among school children in Jhapa, Nepal. Methods: A cross-sectional study was designed to evaluate refractive status of 2236 school children in three government schools and a private school. A complete eye examination was carried out in all children including slit lamp examination, fundus examination, retinoscopy and subjective refraction. Chi-square test was performed to analyze incidence of refractive error in gender; age groups; type of schools. Results: Out of 2236 students, refractive error was present in 192 (8.58%). Unaided, presenting, and corrected visual acuity less than 6/12 (0.5) were present in 3.8%, 2.6%, and 0.2% respectively. After refractive correction, visual acuity was significantly improved (χ2 = 81.3, df = 3, p < 0.01) to 6/6 in 98% students. Forty-five students (2.01%) were amblyopic. Refractive error was significantly prevalent (χ2 = 3.707, df = 1, p = 0.05, ODD = 1.3) in male (9.76%) than in female students (7.48%). refractive error was significantly high in private school than government schools (χ2 = 6.7, df = 1, p < 0.01) Myopia was the most common type (44.79%) of refractive error. The myopia of 2–6 diopters was most common in 48.8%. Myopia was found to increase as age advanced. Hyperopia and astigmatism initially increased but later decreased with age. Conclusions: Refractive error was a significant problem in schoolchildren in Jhapa. Myopia was the most common refractive problem. Private schoolchildren had significantly higher refractive errors.